Hardening of the smart experimental learning / Ahmad Abdul Azim Mansor - Mansor, Ahmad Abdul Azim (2007)
Across the world, there exists a lack of computer security components in many computer science curriculums. For those programs that do have such components in computer security, a common difficulty is to integrate "real-world" labs into the courses, in order to provide hands-on experiences to the learners. Due to concerns for security breaches and network hacking, system administrators are reluctant to allow computer security labs involving network sniffing, virus scripting, etc. to be deployed in the campus network. Without hands-on, real-world projects, it is difficult for the learners to integrate the acquired security theories and knowledge with up-to-date security technologies and practices. For this reason, the purpose of this project paper is to develop and implement a virtual lab module for undergraduate computer security course covering the basics of network security. This project is called Smart Experimental Learning. This virtual lab can be set up for a relatively small investment and allows students to learn attacker techniques and how to defend against them. Little specialized knowledge is required to set up the lab hardware and configure the machines. The hardening process was also being done using various software available. Basically, the results show that the hardening process can be done even the operating systems were installed virtually and students can take this advantage to learn how to harden a system in an environment whereby the results does not effect the real network on the campus. It is hoped that by designing and implementing this virtual lab module successfully, students can learn and experience what we called computer security.